Strategic Directions of the Russian Education Development and their Implementation Ways - V. I. Zagvyazinskiy (Russian State Vocational Pedagogical University, 2015)
The paper deals with the current situation in Russian Education, which is referred to as being in crisis but having a chance for renovation and transformation from its present position of the follower behind the society's demands to the advancing educational system leading to the cultural, social and economic progress of state and society. The non-stability factors of both the global and national type are denoted; the social, personal and economic effects of education are emphasized as being postponed, but affecting both national security and country's political development. The author outlines the strategic reference points for solving the main problems of educational modernization based on the new generation of the Federal educational standards and integrating the traditional and modern educational technologies.